1-{(E)-[(2E)-3-(4-Methoxyphenyl)-1-phenylprop-2-en-1-ylidene]amino}-3-phenylurea: crystal structure and Hirshfeld surface analysis - Tan, Ming Yueh; Crouse, Karen A.; Ravoof, Thahira Begum S. A.; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2017)
The title compound, C23H21N3O2, is constructed about an almost planar disubstituted aminourea residue (r.m.s. deviation = 0.0201 Å), which features an intramolecular amine-N—H...N(imine) hydrogen bond. In the `all-trans' chain connecting this to the terminal methoxybenzene residue, the conformation about each of the imine and ethylene double bonds is E. In the crystal, amide-N—H...O(carbonyl) hydrogen bonds connect centrosymmetrically related molecules into dimeric aggregates, which also incorporate ethylene-C—H...O(amide) interactions. The dimers are linked by amine–phenyl-C—H...π(imine–phenyl) and methoxybenzene-C—H...π(amine–phenyl) interactions to generate a three-dimensional network. The importance of C—H...π interactions in the molecular packing is reflected in the relatively high contributions made by C...H/H...C contacts to the Hirshfeld surface, i.e. 31.6%.